The use of computers and the Internet - effects on employee productivity in Romania - Tofan, Ionela; Aivaz, Kamer-Ainur (Technium Social Sciences Journal, 2022)
The efficient use of the human potential, the increase of the labour productivity is reflected directly or indirectly, in the entire system of economic and financial indicators of the enterprise and on the economy as a whole. In order to create a link between technology/digitalisation and labour we used in this paper the data for the period 2012-2020 for two indicators: Labour productivity per person employed, by activities of the economy (RON/person) taken from the database of the National Institute of Statistics in Romania and Use of computers and the Internet by employees taken from Eurostat (Department of the European Commission responsible for publishing comparable statistics for the entire territory of the EU).